2015
DOI: 10.1177/0093854815604012
|View full text |Cite
|
Sign up to set email alerts
|

Desistance for a Long-Term Drug-Involved Sample of Adult Offenders

Abstract: Using a mixed-race sample of male and female drug-involved offenders who were released from prison in the early 1990s and re-interviewed in 2009 through 2011, this article represents perhaps the first attempt to determine the utility of the identity theory of desistance (ITD) in explaining desistance in a contemporary cohort of adult drug-involved offenders. Supporting the ITD, interview narratives revealed that the vast majority of offenders who successfully desisted from crime and substance misuse had first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 42 publications
4
49
0
4
Order By: Relevance
“…Some researchers have made inroads into the phenomenon of women's desistance as well as shed some light on the risk factors that begin to explain persistent offending patterns among female samples [9,10,21,32,51,52,118]. For example, Cauffman et al [28] compared self-reported offending trajectories for nearly 200 serious female offenders to a matched sample of male offenders and found that among persisters represented in the dataset, women were more likely to have been exposed to violence, trauma, and unhealthy interpersonal relationships.…”
Section: Review Of Empirical Literature On Age and Women's Desistancementioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers have made inroads into the phenomenon of women's desistance as well as shed some light on the risk factors that begin to explain persistent offending patterns among female samples [9,10,21,32,51,52,118]. For example, Cauffman et al [28] compared self-reported offending trajectories for nearly 200 serious female offenders to a matched sample of male offenders and found that among persisters represented in the dataset, women were more likely to have been exposed to violence, trauma, and unhealthy interpersonal relationships.…”
Section: Review Of Empirical Literature On Age and Women's Desistancementioning
confidence: 99%
“…Contemporary studies that do measure the effects of employment on women's self-reported offending and official recidivism are mixed and do not offer much insight into the moderating role of age. While some studies have found that employment status reduces women's offending [22,32,119], other research suggests that having a job in and of itself does not necessarily lead to offending cessation, largely because a host of other criminogenic social and psychological factors has not yet been addressed [9,10,15,99].…”
Section: Review Of Empirical Literature On Age and Women's Desistancementioning
confidence: 99%
See 3 more Smart Citations